Biological efficacy of CalneemTM oil against the tropical warehouse moth Ephestia cautella (Lepidoptera: Pyralidae) in stored maize - Shehu, A.; Obeng-Ofori, D.; Yao Eziah, V. (International Journal of Tropical Insect Science, 2010)
The tropical warehouse moth Ephestia cautella (Walker) is an important storage pest of maize grain. The control of this major moth pest relies heavily on the use of synthetic insecticides. We assessed the biological efficacy of a commercial neem oil (Calneem oil) against E. cautella in the laboratory, using the common grain protectant Actellic as a positive control. Contact toxicity, repellency, effects on oviposition, development and grain damage were assessed. The assays were conducted by treating 100 g of maize grains with Calneem oil concentrations of 3, 5 and 7 ml/l; and Actellic at 2 ml/l. Calneem oil significantly (P < 0.05) reduced oviposition rate, development of eggs and immature stages, and emergence rate of E. cautella progeny in maize grains. Grains treated with Calneem oil had significantly (P < 0.05) reduced grain damage in storage, and the oil had a repellency of 53-70% compared with the negative control. Calneem oil protected maize grain against damage by E. cautella for 10 weeks, compared with 20 weeks protection by Actellic. There was no resistance development to the oil for three generations of E. cautella. The insects that survived treatment with the LC90 concentration (12.2 ml/l) of the Calneem oil laid fewer eggs, and some of their progeny were deformed. Calneem oil provided a good level of protection to maize grains against infestation by E. cautella, and may therefore be a suitable substitute for Actellic. © 2010 icipe.
Keywords: Actellic; Azadirachtin; Calneem oil; Ephestia cautella; Persistence; Repellency; Resistance; Stored maize; Toxicity